2007
DOI: 10.1103/physreve.76.031115
|View full text |Cite
|
Sign up to set email alerts
|

Modeling heat transport through completely positive maps

Abstract: We investigate heat transport in a spin- 2Heisenberg chain, coupled locally to independent thermal baths of different temperature. The analysis is carried out within the framework of the theory of open systems by means of appropriate quantum master equations. The standard microscopic derivation of the weak-coupling Lindblad equation in the secular approximation is considered, and shown to be inadequate for the description of stationary nonequilibrium properties like a non-vanishing energy current. Furthermore,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
275
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(281 citation statements)
references
References 30 publications
6
275
0
Order By: Relevance
“…This setup provides a fully coherent bulk dynamics and incoherent boundary conditions, which is particularly suited for studying nonequilibrium heat transport in a setup similar to the classical case [151]. The Quantum Master Equation (QME) approach can be used to study not only heat transport, but also nonequilibrium processes in general (particle transport, spin transport, etc.).…”
Section: Fourier Law In Quantum Mechanicsmentioning
confidence: 99%
“…This setup provides a fully coherent bulk dynamics and incoherent boundary conditions, which is particularly suited for studying nonequilibrium heat transport in a setup similar to the classical case [151]. The Quantum Master Equation (QME) approach can be used to study not only heat transport, but also nonequilibrium processes in general (particle transport, spin transport, etc.).…”
Section: Fourier Law In Quantum Mechanicsmentioning
confidence: 99%
“…However, Floquet theory has the drawback of converting a finitedimensional problem to an infinite dimensional one. Consequently, most interesting results from Floquet theory are often obtained as a perturbation expansion in terms of inverse drive frequency, giving results primarily for high frequency driving.Moreover, from calculations in the absence of timeperiodic modulations, the commonly used phenomenological Lindblad Quantum Master Equations are known to have several drawbacks, especially in an out-ofequilibrium situation [63][64][65][66]. It has been recently shown that microscopically derived Redfield Quantum Master Equation (RQME) under Born-Markov approximation can be used to overcome the drawbacks of phenomenological Lindblad equations and to obtain correct results up-to leading order in system-bath coupling [63].…”
mentioning
confidence: 99%
“…The SA is an approximation that extracts a slow part of the dynamics; one can obtain L SA by averaging L in time in the interaction picture or by omitting the fast oscillating terms in L in the interaction picture. However, it is known that the internal current vanishes in the NESS of the SA-QME [9]. Therefore, the SA-QME is not appropriate for analyzing the steady state itself (however, note Ref.…”
Section: Decomposition Of Qmementioning
confidence: 99%
“…Therefore, the SA-QME is not appropriate for analyzing the steady state itself (however, note Ref. [46]), and one often uses any of the original Redfield QME, alternatively approximated Lindblad QME [9], or axiomatic Lindblad QME [44,45] for nonequilibrium situations.…”
Section: Decomposition Of Qmementioning
confidence: 99%
See 1 more Smart Citation